Cost-effectiveness analysis of different systolic blood pressure targets for people with a history of stroke or transient ischaemic attack: Economic analysis of the PAST-BP study. (October 2016) - Penaloza-Ramos, Maria Cristina; Jowett, Sue; Barton, Pelham; Roalfe, Andrea; Fletcher, Kate; Taylor, Clare J; Hobbs, FD Richard; McManus, Richard J; Mant, Jonathan
Background: The PAST-BP trial found that using a lower systolic blood pressure target (<130 mmHg or lower versus <140 mmHg) in a primary care population with prevalent cerebrovascular disease was associated with a small additional reduction in blood pressure (2.9 mmHg). Objectives: To determine the cost effectiveness of an intensive systolic blood pressure target (<130 mmHg or lower) compared with a standard target (<140 mmHg) in people with a history of stroke or transient ischaemic attack on general practice stroke/transient ischaemic attack registers in England. Methods: A Markov model with a one-year time cycle and a 30-year time horizon was used to estimate the cost per quality-adjusted life year of an intensive target versus a standard target. Individual patient level data were used from the PAST-BP trial with regard to change in blood pressure and numbers of primary care consultations over a 12-month period. Published sources were used to estimate life expectancy and risks of cardiovascular events and their associated costs and utilities. Results: In the base-case results, aiming for an intensive blood pressure target was dominant, with the incremental lifetime costs being £169 lower per patient than for the standard blood pressure target with a 0.08 quality-adjusted life year gain. This was robust to sensitivity analyses, unless intensive blood pressure lowering reduced quality of life by 2% or more. Conclusion: Aiming for a systolic blood pressure target of <130 mmHg or lower is cost effective in people who have had a stroke/transient ischaemic attack in the community, but it is difficult to separate out the impact of the lower target from the impact of more active management of blood pressure.